Dependence of infrared absorption properties on the Mo doping contents in MxWO3 with various alkali metals. (6th July 2016) - Wang, Tingyu; Xiong, Yuanpeng; Li, Ruixing; Cai, Hongnian
Abstract : Mo doping is an effective process for enhancing the infrared absorption properties of M x WO3 with various alkali metals. Abstract : A series of molybdenum-doped tungsten bronzes with various alkali metals were synthesized by a solvothermal process using ethanol and acetic acid as solvents. All the X-ray diffraction (XRD) peaks for the samples could be indexed as the corresponding types of hexagonal tungsten bronzes with the general formula, M x WO3, where M denotes an alkali metal. Targeted research on cesium tungsten bronze indicates that the actual atomic ratio of Cs to W ( x ) could be influenced by the introduction of molybdenum, which has a critical effect on the infrared absorption properties. Optical tests show that molybdenum-doping is an effective process, with respect to enhancing the absorption of infrared and the conversion efficiency of light energy to heat energy, for tungsten bronzes with various alkali metals. The optimum starting Mo/W (mol) ratios for obtaining high infrared absorption properties were 0.01 for sodium and potassium tungsten bronzes and 0.03 for rubidium and cesium tungsten bronzes. Among the samples, doped cesium tungsten bronze has the strongest properties.